Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the equation [tex]\( x^2 = 5 - x \)[/tex] using the quadratic formula, let's follow the steps below in a detailed manner:
1. Rewrite the equation in standard form:
[tex]\[ x^2 + x - 5 = 0 \][/tex]
In this form, we can identify the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] for the quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex]:
[tex]\[ a = 1, \quad b = 1, \quad c = -5 \][/tex]
2. Apply the quadratic formula:
The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
3. Substitute the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] into the formula:
[tex]\[ x = \frac{-(1) \pm \sqrt{(1)^2 - 4(1)(-5)}}{2(1)} \][/tex]
4. Simplify inside the square root:
[tex]\[ b^2 - 4ac = 1^2 - 4(1)(-5) = 1 + 20 = 21 \][/tex]
5. Plug this back into the formula:
[tex]\[ x = \frac{-1 \pm \sqrt{21}}{2} \][/tex]
Thus, the solutions to the equation are:
[tex]\[ x = \frac{-1 + \sqrt{21}}{2} \quad \text{and} \quad x = \frac{-1 - \sqrt{21}}{2} \][/tex]
Conclusion:
The values of [tex]\( x \)[/tex] that satisfy the equation [tex]\(x^2 = 5 - x\)[/tex] are:
[tex]\[ \boxed{\frac{-1 \pm \sqrt{21}}{2}} \][/tex]
1. Rewrite the equation in standard form:
[tex]\[ x^2 + x - 5 = 0 \][/tex]
In this form, we can identify the coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] for the quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex]:
[tex]\[ a = 1, \quad b = 1, \quad c = -5 \][/tex]
2. Apply the quadratic formula:
The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
3. Substitute the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex] into the formula:
[tex]\[ x = \frac{-(1) \pm \sqrt{(1)^2 - 4(1)(-5)}}{2(1)} \][/tex]
4. Simplify inside the square root:
[tex]\[ b^2 - 4ac = 1^2 - 4(1)(-5) = 1 + 20 = 21 \][/tex]
5. Plug this back into the formula:
[tex]\[ x = \frac{-1 \pm \sqrt{21}}{2} \][/tex]
Thus, the solutions to the equation are:
[tex]\[ x = \frac{-1 + \sqrt{21}}{2} \quad \text{and} \quad x = \frac{-1 - \sqrt{21}}{2} \][/tex]
Conclusion:
The values of [tex]\( x \)[/tex] that satisfy the equation [tex]\(x^2 = 5 - x\)[/tex] are:
[tex]\[ \boxed{\frac{-1 \pm \sqrt{21}}{2}} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.